DETERMINANTS AFFECTING EARNINGS PERSISTENCE - Monica Salim; Sufiyati Sufiyati (International Journal of Application on Economics and Business, 2026)
Investors rely on financial reports, especially earnings, to analyze and help make decisions. Earnings persistence shows that a company can sustain stable earnings despite unpredictable events and uncertain conditions. This study is carried out to gain empirical insights on how several factors, such as leverage, firm size, sales volatility, cash flow volatility, and book-tax difference, influence earnings persistence in consumer non-cyclical manufacturing companies listed on the IDX (Indonesia Stock Exchange) from the year 2022 to 2024. Purposive sampling was applied in this study, resulting in 78 samples. The analysis was conducted with moderated regression analysis, utilizing the software Eviews 12 SV. The results from this research show that leverage negatively and significantly affects earnings persistence, while sales volatility positively and significantly affects earnings persistence. In contrast, firm size, cash flow volatility, and book–tax differences insignificantly impact earnings persistence. Based on these findings, management should control its use of debt to a minimum level and focus on increasing company sales to maintain earnings persistence over time. Researchers in the future are encouraged to examine other variables affecting earnings persistence or extend the research to broader sectors.